Comparison of Comprehension and Remembering from the Lead and Body Parts of Online News - Gumus, Agah; Dabaj, Fahme (Expert Projects Publishing, 2018)
Technological developments proliferated and expedited news taking. In addition to traditional media, on-line newspapers provide the news. The news on on-line newspapers is constantly updated. Lead and body parts of the news have been around for more than a century. Also, research into comprehension and remembering of the news from the traditional media is around for over half a century. Yet, no research is conducted to test comprehension and remembering from the lead and body parts of the news. The present study aims at exploring comprehension and remembering from the lead and body parts of three on-line newspapers. Two pieces of news are chosen from each of the three newspapers and presented to tertiary students either as the lead or the body of the news. Following the exposure, the participants were asked to answer the factual questions. The results of the study suggest that the lead is ultimately more important for the tertiary students than the body of the news. In line with this, comprehension and remembering scores yield higher results for the lead part when compared to the body part of the news.
Keywords: news; lead length; body length; comprehension and remembering; audience